Adolescent body mass index and erythrocyte sedimentation rate in relation to colorectal cancer risk. Issue 8 (18th May 2015) - Kantor, Elizabeth D; Udumyan, Ruzan; Signorello, Lisa B; Giovannucci, Edward L; Montgomery, Scott; Fall, Katja
Abstract : Objective: Adult obesity and inflammation have been associated with risk of colorectal cancer (CRC); however, less is known about how adolescent body mass index (BMI) and inflammation, as measured by erythrocyte sedimentation rate (ESR), relate to CRC risk. We sought to evaluate these associations in a cohort of 239 658 Swedish men who underwent compulsory military enlistment examinations in late adolescence (ages 16–20 years). Design: At the time of the conscription assessment (1969–1976), height and weight were measured and ESR was assayed. By linkage to the national cancer registry, these conscripts were followed for CRC through 1 January 2010. Over an average of 35 years of follow-up, 885 cases of CRC occurred, including 501 colon cancers and 384 rectal cancers. Cox regression was used to estimate adjusted HRs and corresponding 95% CIs. Results: Compared with normal weight (BMI 18.5 to <25 kg/m 2 ) in late adolescence, upper overweight (BMI 27.5 to <30 kg/m 2 ) was associated with a 2.08-fold higher risk of CRC (95% CI 1.40 to 3.07) and obesity (BMI 30+ kg/m 2 ) was associated with a 2.38-fold higher risk of CRC (95% CI 1.51 to 3.76) (p-trend: <0.001). Male adolescents with ESR (15+ mm/h) had a 63% higher risk of CRC (HR 1.63; 95% CI 1.08 to 2.45) than those with low ESR (<10 mm/h) (p-trend: 0.006). Associations did not significantly differ by anatomic site. Conclusions: Late-adolescent BMI and inflammation, as measured by ESR, may be independently associated with future CRC risk. Further research is needed to better understand how early-life exposures relate to CRC.